The Role of Thegulf Region’s Energy Suppliers in China’s Energy Security Policyat the Turn of the 21st Century - Abajyan, Aram (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The main purpose of this article is to analyze China’s energy security calculations starting from the end of the 20th century. The growing demand for oil paved the way for China to expand energy ties especially with the Gulf region’s energy producers. Beijing’s economic modernization initiative together with its market-oriented economic plans caused significant increases in its energy demands. The Gulf attracted China more than any other region due to its huge energy resources.
Keywords: International relations